A Comparison of Humiliation Measurement in a Depressive Versus Non‐clinical Sample: A Possible Clinical Utility. Issue 12 (14th August 2015) - Collazzoni, A.; Capanna, C.; Bustini, M.; Marucci, C.; Prescenzo, S.; Ragusa, M.; Tosone, A.; Di Ubaldo, V.; Stratta, P.; Rossi, A.
Abstract : Objective: We aimed to deepen the clinical utility of humiliation assessment in the study of depression. Method: We performed a correlational analysis of the relationship between humiliation, depression, resilience, and negative primary familial environment in 80 clinically depressed subjects (41 men and 39 women; mean age = 40.71, standard deviation SD = 9.94) and a strictly matched sample of 80 non‐clinical subjects (41 men and 39 women; mean age = 40.64, SD = 10.24). We also implemented a hierarchical multiple regression analysis for each sample, to test the prediction of these variables on depression. Results: Humiliation showed positive correlations with depressive factors, while negative correlations emerged with resilience in both samples. The hierarchical multiple regression analysis showed humiliation to be the most predictive factor of depression in the clinical sample only. Conclusion: This study improves the understanding of the relationship of humiliation and depression in both clinical and non‐clinical populations.